Jogos eletrônicos gratuitos para o ensino da matemática: levantamento e proposta de um recurso didático - Floret, Helder França (2013)
This dissertation presents the survey of one hundred and two games for teaching mathematics that are freely available on the internet. The survey has substantiated the proposal of a new game, called Euclidean, an educational resource for teaching combinatorics. The overarching question of the investigation was: how do electronic games can contribute to the teaching of mathematics and, more specifically, how can they serve as a didactic resource for teaching combinatorics? The methodological approach was qualitative, exploratory, with survey and classification of 102 electronic games. The first phase of the research was devoted to the construction of a theoretical framework, which articulated studies on math education, information and communication technologies, electronic games and combinatorics. In the second-phase, dedicated to data collection, one hundred and two games that could promote the learning of mathematics were identified and categorized. The products of this dissertation were: a game of combinatorics called Euclidean, a new set of criteria for the classification of educational electronic games, and a book for teachers training. Regarding the results of the study, most games prioritized repetition, not the construction of the concepts, which configures the use of new technology in the reproduction of traditional teaching models. The approach to contents was limited to basic mathematical operations. The presence of content designed for high school was rare. Another important aspect was the lack of user interaction. In most cases the player was supposed to follow a script, repeatedly, along stages. Opportunities to change the course of the game or customize it were not offered. Despite these limitations, the study revealed that electronic games may serve as teaching resources for mathematics in basic education, bring closer the world of students and teachers. It also reduces barriers for the development of abstract thinking, enriching learners’ experience. It should be noted, however, the limitations of online games, as well as difficulties for the development of learning objects to the teaching of mathematics.